COVID-19-associated hypertriglyceridemia and impact of treatment - Kaddoura, Rasha; Mohamed Ibrahim, Mohamed Izham; Al-Amri, Maha; Prabhakaran Nair, Arun; Alharafsheh, Ahmad; Alyafei, Sumaya Alsaadi; Albakri, Mutaz (Frontiers in Medicine, 2024)
Background Coronavirus disease 2019 (COVID-19) associated hypertriglyceridemia was observed among patients admitted to intensive care units (ICU) in Qatar. This study aimed to describe COVID-19-associated-hypertriglyceridemia in ICU patients and the impact of treating hypertriglyceridemia on clinical outcomes. Methods A retrospective observational cohort study of adult patients who were admitted to the ICU with a confirmed diagnosis of COVID-19 pneumonia according to the World Health Organization criteria. Hypertriglyceridemia was defined as triglyceride level of 1.7 mmol/L (≥150 mg/dL) and severe hypertriglyceridemia as fasting TG of ≥5.6 mmol/L (≥500 mg/dL). Results Of 1,234 enrolled patients, 1,016 (82.3%) had hypertriglyceridemia. Median age was 50 years and 87.9% were males. Patients with hypertriglyceridemia showed significantly longer time to COVID-19 recovery, ICU and hospital stay, and time to death (29.3 vs. 16.9 days) without a difference in mortality between groups. Of patients with hypertriglyceridemia, 343 (33.8%) received treatment (i.e., fibrate and/or omega-3). Patients in treatment group showed longer time to COVID-19 recovery and hospital stay with no difference in death rates in comparison with those in no-treatment group. Relatively older patients were less likely to experience hypertriglyceridemia (odd ratio (OR) 0.976; 95% CI: 0.956, 0.995) or to receive treatment (OR 0.977; 95% CI: 0.960, 0.994). Whereas patients who received tocilizumab were more likely to experience high TG level (OR 3.508; 95% CI: 2.046, 6.015) and to receive treatment for it (OR 2.528; 95% CI: 1.628, 3.926). Conclusion Hypertriglyceridemia associated with COVID-19 did not increase death rate, but prolonged time to death and length of stay. Treating hypertriglyceridemia did not translate into improvement in clinical outcomes including mortality.